Suicidal Ideation of Healthcare Workers During COVID-19: An Ecological Momentary Assessment - Genest, Christine; Bergeron, Nicolas; Provost-Tremblay, Émilie; Dufour, Marie-Michèle; Guay, Stéphane; Geoffrion, Steve (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2022)
Introduction: The COVID-19 pandemic had an impact on the psychological health of healthcare workers (HCWs). Cross-sectional studies report suicidal ideation in this population during this period, but no longitudinal study has examined the evolution of these ideas over time.Objectives: To assess the evolution of suicidal ideation of HCWs during the first two waves of the COVID-19 pandemic among Quebec (Canada) HCWs and to identify the risk factors involved.Methods: A longitudinal study among Quebec (Canada) HCWs using ecological momentary assessment was conducted between May 8, 2020, and March 31, 2021 (corresponding to the second half of the first wave to the end of the second). Participants (n=865) answered weekly questions related to anxiety (GAD-7), depression (PHQ-9), suicidal ideation (PHQ-9 Q.9), exposure to COVID-19, exposure to COVID-19-related deaths, their infection status and that of their co-workers and loved ones, as well as the amount of time they spent consuming news related to COVID-19.Results: Proportion of suicidal ideation increased from May to June 2020 (second half of the first wave) peaking at 18% before declining up to March 2021. Anxiety and depression symptoms severity increased those ideations as well as having a colleague confirmed positive to COVID-19. Social support does not appear to be a protective factor for suicidal ideation. Suicidal thoughts are associated with media consumption and appear to be mediated by the presence of clinical distress expressed as depressive or anxiety states.Discussion and conclusion: Media consumption in a pandemic context is associated with anxiety and depression, the more severe states of which may express suicidal ideation. Without inferring causality relationship, it seems advisable for HCWs to limit their media exposure during a disaster such as a pandemic.